Acute effects of different stretching protocols on vertical jump and sprinting ability in college soccer players. (Revista horizonte, 2013)
The purpose of this study was to evaluate the acute effect of different stretching protocols on the vertical jump and 20-meter sprint capacity in selected soccer players of the Universidad San Sebastián, Puerto Montt campus. Methods: Quasi-experimental study. 24 soccer players were assigned to 3 groups: Dynamic Stretching (DS) (n=8), Static Stretching (DS) (n=8) and No Stretching (NS) (n=8). After each group performed their respective stretching protocol, the following were evaluated: Vertical jump and 20-meter sprint using a jumping platform. Results: According to ANOVA, there was a significant improvement of vertical jump using ED protocols over EE and NE protocols in; Flight Time (p=0.046) and take-off speed (p=0.045) after ED over EE and height (p=0.049) after ED over EE. Kruskal-Wallis indicates that there are significant differences between sprinting after the different stretching protocols (p=0.006), the NE increased running speed expressed in a shorter running time (2.58 s), with respect to the ED (2.99 s) and EE (3.23 s). Conclusion: The acute effect of the ED is more effective in the vertical jumping capacity than the EE and NE protocol, but the results obtained after the sprint show that the NE is even better than performing an ED or EE protocol.